2006
DOI: 10.1007/s00223-005-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty Genes Are Expressed in Osteoblasts and Inhibit Fibroblast Growth Factor-Mediated Osteoblast Responses

Abstract: Fibroblast growth factors (FGFs) and fibroblast growth factor receptors (FGFRs) are major regulators of skeletal growth and development. Signal transduction via FGFRs is complex and mediates proliferation, differentiation, or migration depending upon the cellular context. Members of the Spry gene family antagonize the FGFR signal transduction pathway and inhibit lung morphogenesis, angiogenesis, and chondrogenesis. We examined the expression of Spry2 in the osteoblastic MC3T3-E1 cell line. MC3T3-E1 cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…GST Pulldown Assays-All of the GST-fused proteins were purified from Escherichia coli as described previously (25). For pulldown assays, the cells were rinsed once with PBS and lysed with the HNTG lysis buffer (20 mM HEPES, pH 7.4, 150 mM NaCl, 10% glycerol, 1% Triton X-100, 1.5 mM MgCl 2 , 1.0 mM EGTA, 1 mM sodium orthovanadate, 1 mM sodium fluoride, and EDTA-free protease inhibitor mixture).…”
Section: Methodsmentioning
confidence: 99%
“…GST Pulldown Assays-All of the GST-fused proteins were purified from Escherichia coli as described previously (25). For pulldown assays, the cells were rinsed once with PBS and lysed with the HNTG lysis buffer (20 mM HEPES, pH 7.4, 150 mM NaCl, 10% glycerol, 1% Triton X-100, 1.5 mM MgCl 2 , 1.0 mM EGTA, 1 mM sodium orthovanadate, 1 mM sodium fluoride, and EDTA-free protease inhibitor mixture).…”
Section: Methodsmentioning
confidence: 99%
“…This effect is related to increased EGFR and PDGFRα expression and signaling induced by activated FGFR2 mutations, an effect which is mediated by both PKCα-mediated AP-1 transcriptional activation and a posttranscriptional mechanism involving Sprouty2 (Spry2). Spry2 acts as a feedback inhibitor of FGF-induced osteoblast response (Yang et al, 2006). FGFR2 activating mutations in osteoblasts promote the CblSpry2 interaction, which sequesters Cbl away from the EGFR, thereby impeding EGFR degradation and increasing EGFR abundance and signaling (Miraoui et al, 2010).…”
Section: Novel Aspects Of Fgf/fgfr Signaling In the Control Of Osteobmentioning
confidence: 99%
“…The Sprouty (Spry) family of proteins was originally identified as feedback inhibitors of fibroblast growth factor receptor signaling [1719] and subsequent studies showed that other RTK signaling pathways such as VEGF are also inhibited by Spry [2022]. Four mammalian Spry genes have been identified, and all of them are expressed in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%